Design, synthesis and anti-inflammatory effects of novel 9-O-substituted-berberine derivatives12. Issue 4 (25th January 2016) - Huang, Mei-Yan; Lin, Jing; Huang, Zhi-Jian; Xu, Hong-Gui; Hong, Juan; Sun, Ping-Hua; Guo, Jia-Liang; Chen, Wei-Min
Abstract : A series of novel 9- O -substituted-berberine derivatives were synthesized and their anti-inflammatory activities were evaluated. Among them, compounds3i and5e exhibited excellent anti-inflammatory potential. Abstract : Berberine, an isoquinoline alkaloid in many medicinal herbs, has been found to possess broad pharmacological activities. A series of novel C-9- O -substituted-berberine derivatives have been synthesized and their anti-inflammatory effects evaluated both in vitro and in vivo . Compared to berberine, the new synthetic berberine derivatives3i and5e exhibit significantly improved inhibitory activities against the release of NO, TNF-α and IL-6. Furthermore, derivatives3i and5e were found to inhibit more effectively the migration of neutrophils and primitive macrophage in transgenic zebrafish larvae with injury-provoked inflammation. Pre-treatment with derivatives3i or5e could lead to a concentration-dependent decrease in nuclear factor-κB (NF-κB) p65 and NF-κB inhibitor α (IκBα) phosphorylation and inducible nitric oxide synthase (iNOS) expression in lipopolysaccharide (LPS)-induced RAW264.7 cells, which suggested that the anti-inflammatory activities of berberine derivatives3i and5e are related to their suppression of the NF-κB signal pathway.